Two distinct waves of greening in northeastern Canada: summer warming does not tell the whole story. (1st June 2022) - Bayle, Arthur; Roy, Alexandre; Dedieu, Jean-Pierre; Boudreau, Stéphane; Choler, Philippe; Lévesque, Esther
Abstract: Arctic vegetation cover has been increasing over the last 40 years, which has been attributed mostly to increases in temperature. Yet, the temporal dimension of this greening remains overlooked as it is often viewed as a monotonic trend. Here, using 11 year long rolling windows on 30 m resolution Landsat data, we examined the temporal variations in greening in north-eastern Canada and its dependence on summer warming. We found two significant and distinct waves of greening, centred around 1996 and 2011, and observed in all land cover types (from boreal forest to arctic tundra). The first wave was more intense and correlated with increasing summer temperature while no such relation was found for the weaker second wave. More specifically, the greening lasted longer at higher elevation during the first wave which translates to a prolonged correlation between greening and summer warming compared to low-altitude vegetation. Our work explored a forsaken complexity of high latitude greening trends and associated drivers and has raised new questions that warrant further research highlighting the importance to include temporal dimension to greening analyses in conjunction with common spatial gradients.